Enhanced AmB Production in Streptomyces nodosus by Fermentation Regulation and Rational Combined Feeding Strategy - Zhang, Bo; Zhang, Yu-Han; Chen, Yu; Chen, Kai; Jiang, Sheng-Xian; Huang, Kai; Liu, Zhi-Qiang; Zheng, Yu-Guo (Frontiers in Bioengineering and Biotechnology, 2020)
Amphotericin B is a clinically important polyene macrolide antibiotic with broad-spectrum antifungal activity. In this work, the addition of key precursors and differential metabolites combined with staged fermentation process control strategies were carried out to improve AmB production. Rationally designed addition strategies were proposed as follows: 4 mg/L isopropanol, 1 mM alanine, 1 g/L pyruvate and 0.025 g/L nicotinamide were supplemented at 24 h. The AmB titer was ultimately enhanced to 6.63 g/L with 28.5% increase in shake flasks fermentation. To further promote the biosynthesis of AmB, different glucose feeding strategies were investigated and the highest AmB titer (15.78 g/L) was obtained by constant speed fed-batch fermentation in 5-L fermentor. Subsequently, compared with the batch fermentation (9.89 g/L), a novel combined feeding strategy was ultimately developed to improve the production of AmB by 85.9%, reaching 18.39 g/L that is the highest yield of AmB ever reported so far, in which the optimized components were fed at h and the staged fermentation regulation strategies were used simultaneously.Moreover, the ratio of co-metabolite AmA decreased by 32.3% from 3.1% to 2.1%.Through extracellular organic acids detection, the change of α-ketoglutaric acid, pyruvate, citric acid and lactic acid concentration were identified as the more flexible metabolites nodes to further clarify the potential mechanism under different fermentation regulation strategies. These results demonstrated that the strategies above may provide new guidance for industrial scale production of AmB.